2018
DOI: 10.1080/00131911.2018.1536035
|View full text |Cite
|
Sign up to set email alerts
|

Improving narrative writing skills through observational learning: a study of Swedish 5th-grade students

Abstract: Observational learning is a successful method for improving writing skills in various genres. We explore effects of a five lesson intervention series based on peer observation. Fifty-five Swedish 5th-grade students aged 10-12 years followed this intervention programme. The students watched short film clips with peers working with texts. Each lesson was organised according to a theme: reader's perception of the text, ordering of events, how to begin a story, how to end a story and how to edit a text. The studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 31 publications
2
34
0
3
Order By: Relevance
“…working memory capacity, language comprehension, and reading comprehension) were assessed, and data on audiological factors were collected. The present study is part of a comprehensive study in which students with NH and students with HL followed the same writing intervention [36].…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…working memory capacity, language comprehension, and reading comprehension) were assessed, and data on audiological factors were collected. The present study is part of a comprehensive study in which students with NH and students with HL followed the same writing intervention [36].…”
Section: The Present Studymentioning
confidence: 99%
“…The students' writing performance was assessed four times: one week before and one week after the writing intervention (see below), after another six weeks, and once more after the summer vacation five months later. The same time intervals between the first three texts were also used by Grenner et al [36]. The topics of the four texts were, respectively: 1) Write about a time when you were saved from a jam, or when you saved someone else from a jam; 2) Write about a time when you were hurt; 3) Write about a time when you were afraid; 4) Write about a time when you made somebody happy.…”
Section: Narrative Texts and Text Quality Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many opinions say that writing skills can be improved by improving the narrative text writing skills [9]- [11]. Narrative text is defined as a type of text that aims to tell an event to entertain the reader and has moral values in the story [12], [13]. The hallmark of narrative texts is that they have a structured organizational structure including orientation, complications, and resolution [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the use of learning strategies or methods is the most influential factor. Grenner's research shows that the use of observation method can improve students' skills in writing primary school class narratives in Sweden [13]. However, according to Slamet, the use of teaching material also has a big influence because it can provide support in writing process.…”
Section: Introductionmentioning
confidence: 99%